2001
DOI: 10.1097/00005768-200106001-00020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on glucose homeostasis in Type 2 diabetes mellitus

Abstract: It is uncertain whether there is a dose-response effect of exercise on improved glucose control in Type 2 DM. There does appear to be, however, a limited amount of evidence suggesting that increasing levels of physical activity contribute to better diabetes prevention. Clearly, additional studies are needed to determine the influence of physical activity on the treatment and prevention of Type 2 DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
3

Year Published

2002
2002
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(56 citation statements)
references
References 37 publications
3
50
0
3
Order By: Relevance
“…Physical activity, considered to be an integral component of diabetes management [7,8], has been shown to be associated with improved glucose control and a reduction in long-term complications [37][38][39]. Similarly to others who have found the Ala to be less frequent in individuals with type 2 diabetes than controls [17,24,40], 16% of our type 2 diabetic population carried at least one Ala allele (vs 21% in non-diabetic cohorts [21,26]), a frequency comparable with previous reports from diabetic populations [21].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity, considered to be an integral component of diabetes management [7,8], has been shown to be associated with improved glucose control and a reduction in long-term complications [37][38][39]. Similarly to others who have found the Ala to be less frequent in individuals with type 2 diabetes than controls [17,24,40], 16% of our type 2 diabetic population carried at least one Ala allele (vs 21% in non-diabetic cohorts [21,26]), a frequency comparable with previous reports from diabetic populations [21].…”
Section: Discussionmentioning
confidence: 99%
“…10,11,16 Experimental data have shown that increases in physical activity improve each metabolic syndrome risk factor. [17][18][19][20][21] Cross-sectional studies, 22,23 including our analyses in the Aerobics Center Longitudinal Study (ACLS), 24,25 have demonstrated an inverse association for physical activity and cardiorespiratory fitness with metabolic syndrome prevalence. Furthermore, a recent study showed that participation in 20 weeks of supervised aerobic exercise training resulted in a 31% reduction in metabolic syndrome prevalence among 105 adults.…”
Section: See P 453mentioning
confidence: 96%
“…33 Regular physical activity is a low-cost, safe therapy with minimal adverse side effects 33 and favorable benefits on a broad spectrum of health parameters, 28,29,34 including each metabolic syndrome component. [17][18][19][20][21] Pharmacological intervention for metabolic syn- drome would require multiple agents, which increases costs and risks of adverse effects. Therefore, promoting higher population levels of cardiorespiratory fitness through greater physical activity may be the most prudent clinical and public health strategy for the primary prevention of metabolic syndrome.…”
Section: Lamonte Et Al Fitness and Metabolic Syndrome Riskmentioning
confidence: 99%
“…Exercise training and lifestyle counselling can favourably modify blood pressure (14,15), serum triglyceride levels, highdensity lipoprotein cholesterol (16)(17)(18), insulin sensitivity and glucose homeostasis (19). Psychosocial problems, such as depression and anxiety, are negatively associated with prognosis.…”
Section: Efficacy Of Crmentioning
confidence: 99%